1997
DOI: 10.1111/j.1939-1676.1997.tb00093.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Potassium Content and Potassium Gluconate Supplementation in Normokalemic Cats With Naturally Occurring Chronic Renal Failure

Abstract: Muscle potassium content and supplementation with potassium gluconate were evaluated in normokalemic cats with chronic renal failure (CRF). Affected cats received standard medical therapy for renal failure and either placebo (sodium gluconate) or potassium gluconate. At the beginning of the study and after 6 months of supplementation, glomerular filtration rate (GFR) and effective renal plasma flow (ERPF) were estimated using 3H-inulin and '4C-tetraethylammonium bromide (TEA) clearances. Muscle potassium conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 12 publications
1
10
1
3
Order By: Relevance
“…In cats, hypokalemic myopathy typically is associated with chronic renal disease and poorly regulated diabetes mellitus. 2,8,12 In the myocardial cell, a high intracellular/extracellular potassium concentration ratio induces a state of electrical hyperpolarization leading to prolongation of the action potential. 14 More recently feline hyperaldosteronism as a result of aldosteronoma and adrenocortical hyperplasia has been described, although a diagnostic workup for these conditions is only indicated if the more common etiologies are not present.…”
Section: Consequencesmentioning
confidence: 99%
“…In cats, hypokalemic myopathy typically is associated with chronic renal disease and poorly regulated diabetes mellitus. 2,8,12 In the myocardial cell, a high intracellular/extracellular potassium concentration ratio induces a state of electrical hyperpolarization leading to prolongation of the action potential. 14 More recently feline hyperaldosteronism as a result of aldosteronoma and adrenocortical hyperplasia has been described, although a diagnostic workup for these conditions is only indicated if the more common etiologies are not present.…”
Section: Consequencesmentioning
confidence: 99%
“…7 Therefore, it is thought that serum potassium concentrations may not be representative of intracellular potassium concentrations as normokalemic cats with CKD have been demonstrated to have lower muscle potassium concentrations than normal control cats. 6 Clinical signs of moderate-to-severe hypokalemia can include muscle weakness, particularly cervical ventroflexion, polyuria and polydipsia, tachycardia, constipation and anorexia. 4 Although hypokalemia has not been shown to be a risk factor for disease progression or outcome in CKD cats, 8,9 studies in CKD cats have demonstrated improvement in renal function when normokalemia was restored with potassium supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…A hipercalcemia, conseqüente à IRC pode decorrer da diminuição da eliminação de cálcio e de PTH, bem como de seus metabólitos, pelos rins devido a baixa taxa de filtração glomerular, como também pelo aumento na formação de complexos cálcicos séricos estimulado pelo PTH, pela diminuição da sensibilidade da paratireóide ao cálcio sérico e do aumento da sensibilidade dos receptores intestinais para calcitriol, devido ao baixo nível de calcitriol sérico MEUTEN, 1982;KRUGER et al, 1996). , 1986;POLZIN et al, 2001;THEISEN et al, 1997). No presente estudo, a freqüência de hipopotassemia em 15,8% dos casos de IRC foi menor quando comparada aos relatos anteriores, possivelmente pelo fato de que alguns animais encontravam-se em terapia de suplementação oral de potássio (gluconato de potássio).…”
Section: Discussionunclassified
“…De acordo com um estudo realizado por Theisen et al (1997), a administração de gluconato de potássio assegura a manutenção de níveis séricos estáveis de potássio, entretanto, a presença de valores séricos normais de potássio não exclui a possibilidade de défice orgânico de potássio, uma vez que gatos com IRC, normocalêmicos, apresentavam valores diminuídos de potássio muscular, quando comparados com gatos sadios.…”
Section: Discussionunclassified